2011
DOI: 10.5688/ajpe75343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacy Students' Communication Competence Using the Roter Interaction Analysis System During Objective Structured Clinical Examinations

Abstract: Objective. To determine the value of using the Roter Interaction Analysis System during objective structured clinical examinations (OSCEs) to assess pharmacy students' communication competence. Methods. As pharmacy students completed a clinical OSCE involving an interview with a simulated patient, 3 experts used a global rating scale to assess students' overall performance in the interview, and both the student's and patient's languages were coded using the Roter Interaction Analysis System (RIAS). The coders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
8
0
5
Order By: Relevance
“…Previous pharmacy studies that have used RIAS were in the context of structured pharmaceutical care consultations, 65 and assessment of pharmacy students' interview skills. 66 In this study, it was found that RIAS was also wellsuited to describe brief consultations taking place at community pharmacy counters, and to assess core elements of patient-centered communication.…”
Section: Discussionmentioning
confidence: 97%
“…Previous pharmacy studies that have used RIAS were in the context of structured pharmaceutical care consultations, 65 and assessment of pharmacy students' interview skills. 66 In this study, it was found that RIAS was also wellsuited to describe brief consultations taking place at community pharmacy counters, and to assess core elements of patient-centered communication.…”
Section: Discussionmentioning
confidence: 97%
“…O desenvolvimento e a avaliação da competência de comunicação são uma tarefa complexa, pois envolve empatia, clareza, objetividade, segurança, entre outros requisitos. Nessa revisão alguns pesquisadores utilizaram a simulação como estratégia para o desenvolvimento da comunicação em diferentes contextos, abrangendo: as entrevistas clínicas, a comunicação de más notícias, as orientações de procedimentos ou tratamentos a serem realizados, e, também, o relacionamento interprofissional da equipe de saúde [18][19][20]26,27,30,36 .…”
Section: Discussionunclassified
“…Using IPA derivatives, fully adapted to the specific content of the communication between providers and patients in different settings, was advantageous to the study objectives. RIAS is a widely used method for coding health professional–patient communication, which has shown its utility and applicability for pharmacists' interviews . Based on a coding scheme of 40 categories, RIAS allows allocation for each recorded unit (i.e.…”
Section: Methodsmentioning
confidence: 99%